2008
DOI: 10.1097/tp.0b013e318188d433
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Cells of Monocyte Lineage Prevents Loss of Renal Microvasculature in Murine Kidney Transplantation

Abstract: These data indicate a significant role for macrophages in causing acute rejection-related tissue injury that is, at least in part, targeted to the microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…In contrast, DT administration to CD11b-DTR mice depleted F4/80 + macrophages but did not affect DCs in the spleen and lymph nodes (28). Qi et al noted similar findings using a murine kidney transplantation model that DT treatment in CD11b-DTR mice significantly reduced circulating monocytes, eliminated renal F4/80 + cells, and CD11c + cells, but had no effects on CD11c + DCs in the spleen (29). Thus, susceptibility of CD11c DCs to DT is different among the various organs in CD11b-DTR mice.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, DT administration to CD11b-DTR mice depleted F4/80 + macrophages but did not affect DCs in the spleen and lymph nodes (28). Qi et al noted similar findings using a murine kidney transplantation model that DT treatment in CD11b-DTR mice significantly reduced circulating monocytes, eliminated renal F4/80 + cells, and CD11c + cells, but had no effects on CD11c + DCs in the spleen (29). Thus, susceptibility of CD11c DCs to DT is different among the various organs in CD11b-DTR mice.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, blockade of macrophage colony-stimulating factor-reduced macrophage proliferation and accumulation in the graft leading to a decrease in the severity of kidney transplant rejection in mice (Jose et al 2003). Other studies have confirmed in macrophages a decreased infiltration and an increase in graft survival in murine models of both kidney (Qi et al 2008) and heart (Takeiri et al 2011) transplantation. Furthermore, in the context of human kidney transplantation, CX3CR1 expression by macrophages was associated with acute rejection, and was a negative prognostic factor in human kidney graft (Hoffmann et al 2010).…”
mentioning
confidence: 68%
“…Cellular immunity includes T-cell-mediated cytotoxicity and also natural killer cell-mediated and macrophagemediated cytotoxicity [17][18][19]. Humoral immunity attacks allografts by producing specific antibodies against the grafts [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%